Pathways to care for psychosis in rural Uganda: Mixed-methods study of individuals with psychosis, family members, and local leaders - Yang Jae Lee; Kayera Sumaya Nakaziba; Sophie Waimon; Grace Agwang; Kailash Menon; Sam Samuel; Aaron Damon Dyas; Travor Nkolo; Haba Ingabire; Jason Wykoff; Olivia Hobbs; Rauben Kazungu; et al. (Cambridge Prisms: Global Mental Health)
Abstract